Hearing health inequalities in Culturally and Linguistically Diverse communities in Australia. - de Silva, Dumini (My University, 2025)
Background: Studies from Europe and the USA indicate that Culturally and Linguistically Diverse (CALD) communities experience higher rates of hearing loss. There are no data concerning Australia. Given that approximately one in four Australians has a CALD background, it is crucial to identify possible inequalities in hearing loss among Australians from CALD communities and identify factors that contribute to any inequalities. Objectives: The study aimed to (1) assess the prevalence of hearing loss among children from CALD versus ethnic majority backgrounds, and (2) examine the demographic, socioeconomic, and health factors associated with hearing loss in children from CALD communities. Methods: A sub-set of data from the Longitudinal Study of Australian Children a nationally representative cross-sectional survey, was utilised. Analysis included children aged 11- 12 who underwent pure tone audiometry. CALD status was identified based on having a primary caregiver who spoke a language other than English at home. Logistic regression was used to model correlates of hearing loss. Results: A higher prevalence of hearing loss was found in children from CALD backgrounds (33.8%) compared to the ethnic majority (21.3%). The odds of hearing loss in children from CALD communities were 1.6 times higher after adjusting for sociodemographic and hearing-related factors. Female sex, living in socioeconomically disadvantaged areas, and primary caregiver’s English language proficiency were independently associated with increased odds of having hearing loss among children from CALD backgrounds. Conclusion: Hearing loss is around one third more common among children from CALD backgrounds. Future studies should determine the causal factors and develop strategies for preventing hearing loss and implementing early detection programs for CALD communities to reduce hearing health inequalities.
Keywords: Health and wellbeing